HBR guide to making every meeting matter / Amy Gallo, Elizabeth Grace Saunders, Al Pittampalli... - Gallo, Amy
Meetings. They hold such promise for moving your business forward, but they rarely deliver. We all know the steps we're supposed to take to run an effective meeting, but we seldom follow them. Why? Perhaps it just doesn't seem worth the time to pinpoint what we want to accomplish, craft an agenda, handpick participants, issue prework, and, after the meeting, send out notes summarizing key decisions and next steps. But meeting preparation and follow-up is time well spent. This guide offers practical tips to make your meetings easier to prepare for, more enjoyable to run, and more productive. In time, these steps will become so ingrained you won't be able to imagine running a meeting any other way. You'll learn how to: determine whether you even need to meet manage basic meeting prep orchestrate group decision making get the most out of web- and phone-conferencing tools cope with chronic latecomers, windbags, and other common problems turn a bad meeting around keep the momentum going with prompt meeting follow-up develop a reputation for running great meetings--